2014
DOI: 10.5935/2238-3182.20140139
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of children who are recipients of the Family Allowance Program followed up by the Food and Nutrition Surveillance System in the State of Minas Gerais

Abstract: Introduction: The Family Allowance Program (PBF) consists of a direct transfer of income benefiting families in poverty and extreme poverty in the country. Objective: this study aims to characterize the nutritional state of children less than seven years of age, beneficiaries of PBF and followed up by the Food and Nutrition Surveillance System (SISVAN) in the State of Minas Gerais (MG). Methods: the data were obtained from the SISVAN WEB platform from the database comprising information related to the Basic He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
(21 reference statements)
1
4
0
1
Order By: Relevance
“…Saldanha et al 31 found similar results in children of a capital in the southeast, concluding that the population covered by the Family Grant Programme is going through the process of nutritional transition. This change in food pattern reflects the increase in overall food consumption, including processed foods of high caloric density and low nutritional quality.…”
Section: Discussionsupporting
confidence: 65%
“…Saldanha et al 31 found similar results in children of a capital in the southeast, concluding that the population covered by the Family Grant Programme is going through the process of nutritional transition. This change in food pattern reflects the increase in overall food consumption, including processed foods of high caloric density and low nutritional quality.…”
Section: Discussionsupporting
confidence: 65%
“…6,7 Studies have indicated higher prevalence rates of stunting and overweight/obesity among children from families benefiting from this program. 18,24 These families are more vulnerable to food and nutrition insecurity, with possible losses for the child's nutritional status, both in linear growth potential and weight gain. [24][25][26][27] The relationship between the findings and the greater use of health services by children with nutritional problems might also be possible.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these data, another study carried out with children aged 0-7 years benefiting from the Bolsa Família Program (PBF) in Minas Gerais , monitored by SISVAN in 2008-2011, highlighted the prevalence of low W/A in 2011 of 3.0% of the 11,880 children evaluated. 20 Despite the discording age group, one realizes that in the most vulnerable populations, such as PHC users and PBF recipients, the prevalence of low weight have remained significant over time.…”
Section: Discussionmentioning
confidence: 99%